The Relationship Between Learning Motivation and Learning Outcomes in Indonesian Language Subject: Writing Simple Pantun Material for Grade V Students - Hutagaol, Erixon; Rahmad Kartolo; Harianto II (International Journal of Educational Research Excellence, 2026)
This study aims to determine the relationship between learning motivation and student learning outcomes in the Indonesian language subject, especially in the material of writing simple pantun. The problem raised in this study is the low learning outcomes of students in writing pantun and the alleged influence of their level of learning motivation. The research method used is a quantitative method with a correlational approach. The research sample consisted of 22 grade V students of SDN 22 Pangkatan, who were selected using a simple random sampling technique. Data were collected through a learning motivation questionnaire and learning outcome test. The statistical test used is Pearson Product Moment correlation analysis to determine the relationship between the two variables. The results of the study indicate that there is a significant relationship between learning motivation and learning outcomes in writing simple pantun. The correlation coefficient value (r) = -0.295 with a significance value of p = 0.016 is obtained. Although the correlation is negative, this relationship remains significant at the 5% level, indicating that the higher the students' learning motivation, the better their learning outcomes. The coefficient of determination (R²) is 0.875, which means that learning motivation contributes 87.50% to student learning outcomes, while the remaining 12.50% is influenced by other factors. The conclusion of this study is that learning motivation has a significant impact on student learning outcomes. Therefore, teachers are expected to be able to improve learning strategies that can motivate students, such as the use of more interactive methods, giving awards, and creating a more conducive learning environment